L’Hydro-électricité du Québec : Produire pour consommer ou produire pour exporter? - Landry, Réjean (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1984)
The author looks into the stimulations and constraints with regard to the utilization of Hydro-Quebec' s surplus power in the light of the public choice theory. The study tries to establish the merits of four main propositions. Firstly, the reason behind the significant surplus of electrical energy produced lies more with the means of production of hydro-electricity itself ' than with the decision-makers of Hydro-Quebec. Secondly, due to the stimulations and constraints generated by the institutional arrangements, the Quebec decision-makers tend to prefer a strategy of internal consumption to one of exportation. Thirdly, the exportation strategy is adopted only to make up for the impossibility to get rid of all the surplus on internal markets. Finally, the strategy opted for by the decision-makers in Quebec results in sub-optimal conditions which are more to the advantage of those holding the means of production to the detriment of the consumer.